Cancer related adverse events associated with use of proton pump inhibitors and histamine-2 receptor antagonists: A real-world analysis using the FDA adverse event reporting system - Bowen Wang; Zheyun Song; Shan Lan; Xiubi Chen; Xida Yan; Xue-Feng Jiao (PLoS ONE, 2025)
Despite widespread use, concerns have emerged regarding the increased risks of digestive system cancers associated with use of proton pump inhibitors (PPIs). Moreover, ranitidine was recalled from the market in some countries due to its potential carcinogenicity, which also has raised concern about cancer risk in association with use of histamine-2 receptor antagonists (H2RAs). We comprehensively explored the potential risks of various cancers associated with use of PPIs and H2RAs by analyzing the FDA Adverse Event Reporting System (FAERS), aiming to offer real-world evidence for the safe and rational use of acid suppressive agents. OpenVigil 2.1 was utilized to query the FAERS database. Cancer related adverse events (AEs) included Preferred Terms (PTs) of malignant neoplasms among all cancer sites. Disproportionality analysis was performed, and a positive signal indicated a statistical association between cancer related AEs and drugs. Most PPIs had more cancer related PTs with positive signals than H2RAs (except ranitidine), but had fewer cancer related PTs with positive signals than ranitidine. Forty-three cancer related PTs exhibited positive signals for more than one PPIs, and the major cancer sites of these PTs were gastric, lung, lymphomas, pancreatic, oesophageal, intestinal, upper respiratory tract, renal, soft tissue, and so on. Besides, only two cancer related PTs exhibited positive signals for more than one H2RAs (except ranitidine). Our study suggests that PPIs may be associated with more cancer related AEs than H2RAs (except ranitidine), but may be associated with fewer cancer related AEs than ranitidine. Except for digestive system cancers, use of PPIs may also be associated with increased risks of multiple non-digestive system cancers. According to our findings, H2RAs (except ranitidine) may be safer than PPIs regarding cancer risk, and the priority use of PPIs for acid suppression therapy may not be appropriate.